Coconut Cryopreservation: Present Status and Future Prospects - Welewanni, Iroshini; Jayasekera, Anil; Bandupriya, Dharshani (International Coconut Community Journal, 2017)
Coconut is one of the most important small holder crops worldwide. Conservation of coconut as seeds or field gene banks is not effective due to a range of limitations. Cryopreservation, which is the conservation of living propagules at very low temperature (-196ºC), is the only method available currently for the long-term conservation of germplasm for problem plant species such as recalcitrant and vegetatively propagated plant species. This review summarizes different cryopreservation techniques that have been published from 1984 until the present in relation to different coconut material; it includes a brief discussion about short and medium-term cryopreservation before describing long-term preservation. It discusses factors affecting the process and success of cryopreservation, such as selection of plant material, pre-culture of tissues, osmoprotection, dehydration, cryo-storage, thawing and post-culturing of tissues, and finally to plants. The review also describes histological and ultra-structural studies on and the use of molecular markers to assess genetic stability after cryopreservation. Limitations and future directions related to coconut cryopreservation are discussed. Additional experiments are identified that will need to be undertaken to improve our understanding of the different cryopreservation methods.